2004
DOI: 10.1088/0031-9155/49/20/r01
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized xenon in NMR and MRI

Abstract: Hyperpolarized gases have found a steadily increasing range of applications in nuclear magnetic resonance (NMR) and NMR imaging (MRI). They can be regarded as a new class of MR contrast agent or as a way of greatly enhancing the temporal resolution of the measurement of processes relevant to areas as diverse as materials science and biomedicine. We concentrate on the properties and applications of hyperpolarized xenon. This review discusses the physics of producing hyperpolarization, the NMR-relevant propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
102
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 258 publications
(378 reference statements)
0
102
0
Order By: Relevance
“…Radioactive 133 Xe is used as a tracer for measuring physiological blood flow (1) and also in detecting long-range fallout from nuclear weapons testing (2). Stable isotope 129 Xe has a spin-half nucleus that can be hyperpolarized to generate very large signals for MRI (3). Host molecules have been identified that bind xenon with high affinity (4), motivating further technological applications.…”
mentioning
confidence: 99%
“…Radioactive 133 Xe is used as a tracer for measuring physiological blood flow (1) and also in detecting long-range fallout from nuclear weapons testing (2). Stable isotope 129 Xe has a spin-half nucleus that can be hyperpolarized to generate very large signals for MRI (3). Host molecules have been identified that bind xenon with high affinity (4), motivating further technological applications.…”
mentioning
confidence: 99%
“…[82]). These results have been obtained by clinical research teams participating in the PHIL project (Polarized Helium to Image the Lung), a joint effort of nine European research teams in five countries [83].…”
Section: Current Status Of Researchmentioning
confidence: 99%
“…MRI provides exquisite anatomic images, with high spatial resolution (as good as tens of micrometers for preclinical studies and $1 mm for clinical studies) and excellent soft tissue contrast. Image contrast can often be selectively enhanced utilizing a range of passive contrast agents, some based on paramagnetic atoms, particularly gadolinium [1], some on superparamagnetic iron oxide particles [2], and others on hyperpolarized gases such as xenon [3]. MRI can interrogate aspects of physiology; for example, functional MRI (fMRI) takes advantage of the physiologic consequences of neuronal activation (the BBOLD[ effect) to visualize task-dependent responses [4].…”
Section: Introductionmentioning
confidence: 99%